Synergistic convergence of microbiota-specific systemic IgG and secretory IgA - Fadlallah, Jehane; Sterlin, Delphine; Fieschi, Claire; Parizot, Christophe; Dorgham, Karim; El Kafsi, Hela; Autaa, Gaëlle; Ghillani-Dalbin, Pascale; Juste, Catherine; Lepage, Patricia; Malphettes, Marion; Galicier, Lionel; et al. (Journal of allergy and clinical immunology, 2019)
Commensals induce local IgA responses essential to the induction of tolerance to gut microbiota, but it remains unclear whether antimicrobiota responses remain confined to the gut. The aim of this study was to investigate systemic and intestinal responses against the whole microbiota under homeostatic conditions and in the absence of IgA. We analyzed blood and feces from healthy donors, patients with selective IgA deficiency (SIgAd), and patients with common variable immunodeficiency (CVID). Immunoglobulin-coated bacterial repertoires were analyzed by using combined bacterial fluorescence-activated cell sorting and 16S rRNA sequencing. Bacterial lysates were probed by using Western blot analysis with healthy donor sera. Although absent from the healthy gut, serum antimicrobiota IgG are present in healthy subjects and increased in patients with SIgAd. IgG converges with nonoverlapping secretory IgA specificities to target the same bacteria. Each individual subject targets a diverse microbiota repertoire with a proportion that correlates inversely with systemic inflammation. Finally, intravenous immunoglobulin preparations target CVID gut microbiota much less efficiently than healthy microbiota. Secretory IgA and systemic IgG converge to target gut microbiota at the cellular level. SIgAd-associated inflammation is inversely correlated with systemic anticommensal IgG responses, which might serve as a second line of defense. We speculate that patients with SIgAd could benefit from oral IgA supplementation. Our data also suggest that intravenous immunoglobulin preparations can be supplemented with IgG from IgA-deficient patient pools to offer better protection against gut bacterial translocations in patients with CVID. [Display omitted]